Ambulatory Blood Pressure Monitoring in HIV-Infected Patients: Usefulness for Cardiovascular Risk Assessment. (18th August 2020) - Gómez-Berrocal, Ana; De los Santos-Gil, Ignacio; Abad-Pérez, Daniel; Gutiérrez-Liarte, Ángela; Ibáñez-Sanz, Patricia; Sanz-Sanz, Jesús; Suárez, Carmen
Background: There is a lack of consensus regarding the risk of hypertension in HIV-infected patients compared to the general population. Ambulatory blood pressure monitoring (ABPM) is the most accurate method for the hypertension diagnosis. Nevertheless, it is rarely used in HIV clinical care. Materials and Methods: All HIV-infected patients who underwent 24 hours ABPM were included. The agreement between office blood pressure (BP) readings and ABPM was analyzed. The rate of patients with masked hypertension (MH), isolated clinical hypertension, and nocturnal hypertension was obtained. Furthermore, it was analyzed if the differences between both methods may affect the cardiovascular risk (CVR) assessment. Results: A total of 116 patients were included. The κ coefficient between office BP and ABPM was 0.248. Over a quarter of the cohort was diagnosed with MH—25.8% (CI 95% 17.7%-34.0%), and 12% (CI 95%: 6.1%-16.1%) was diagnosed with ICH. Moreover, 19% of patients had hypertension exclusively during the night. The patients classified as low risk according to the CVR scores had a different diagnosis with ABPM than with office BP ( P < .001). Conclusions: The agreement between office BP and ABPM was low in HIV-infected patients. Ambulatory BP monitoring is useful in HIV-infected patients as a hypertension diagnosis method, especially among patients classified as low risk.